Innovations in Bus Rapid Transit (BRT) in Brazil and China - Maia, Marcelo; Guo, Liang; Carneiro, Davi; Jia, Yihe; Garcia, Nickolas; Dong, Fengqian (International Planning History Society Proceedings, 2024)
Currently, Brazil and China are at the forefront with the largest Bus Rapid Transit (BRT) networks globally. Since the 1970s, Brazil has been building its expertise, spearheading the creation of an industry focused on designing and manufacturing vehicles specifically for the BRT system. These vehicles have undergone continuous innovation in both Brazil and China. This development has occurred alongside enhancements in BRT stations and the adoption of inclusive urban designs, which have transformed the public spaces surrounding the terminals. This transformation has not only introduced new methodologies in urban design but has also elevated the architectural significance of terminal buildings. The innovations span from vehicle and terminal architecture design to specific urban planning, all augmented by the advent of cutting-edge technologies. These technologies facilitate intelligent traffic management within BRT corridors and automate fare collection, marking a significant step toward transforming transportation into a smarter system. This study aims to compare the significant advancements made in Brazil and China, focusing on the synergy between vehicle design, terminal architecture, accessible urban planning, and smart management and ticketing systems. The goal is to underscore how these advancements are propelling public transport towards greater efficiency, sustainability, and intelligence.